Pendekatan Systematic Literature Review: Faktor-faktor Penerimaan Opini Audit Going Concern - Arfandi, Arfandi; Djaddang, Syahril (Jurnal Eksplorasi Akuntansi, 2025)
An external auditor must examine the company's performance as reported in the financial accounts, particularly if it is a publicly traded corporation. To indicate and illustrate the company's capacity to sustain business continuity, auditors can provide a going concern audit opinion, which stakeholders can use as information when making decisions. The Systematic Literature Review (SLR) approach is used in this study. The two primary sources of current research literature that may be used to categorize the factors that impact the acceptability of going concern audit opinions are internal and external considerations. Internal elements that measure the financial performance produced by the organization as a result of management performance include governance, real activity manipulation (RAM), and financial measurements like profitability, liquidity, leverage, or solvency. External variables include the reputation and quality of the auditor, opinion shooping, and financial circumstances that result in financial difficulties brought on by difficult or natural forces like the COVID-19 pandemic.